Analisis Pengaruh Nilai Nasabah dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Untuk Menciptakan Loyalitas Nasabah (Studi Pada Nasabah Bank BRI Cabang Pandanaran Semarang) - Syaepul Mukarom, Moch; Khasanah, Imroatul (Diponegoro Journal of Management, 2012)
The research was motivated by a bank customer complaints Pandanaran Semarang Branch of BRI which indicates a decline in customer satisfaction as well as increase i the number of customer who closed acounts during the three yaers 2009-2011. By looking at existing problems, this study aimed to analyze the influence of customer value and quality of service to the customer satisfaction to creat customer loyalty Pandanaran BRI branch Semarang. This study sample of 100 people Pandanaran Semarang Branch of BRI customers. Question is given by using questionnaire consisting of closed and open questions. Respondentâ€™s answers wetre then analyzed with a two stage regression using SPSS for Windows. Based on the analysis conducted, it was concluded that the variable value and quality customer service and a sidnificant inpact on customer loyalty. The result ofÂ  this study is expected to be used as information for the BRI branch Pandanaran Semarang and further research. Keywords: Banking Industry, Customer Value, Quality Service, Customer Satisfaction, Customer Loyalty.